Metal-Oxide Gas Sensors - Dhara, Soumen; Dutta, Gorachand (IntechOpen, 2023)
This book provides an overview of recent advances in the development of gas sensors for the electronics and healthcare industries that can lead to lifestyle enhancements. We are living in a society where automation is in great demand for all electrical devices and appliances. One of the major requirements for smart devices is highly sensitive, long-lasting, low-cost smart sensors. Existing challenges and future research directions for easy integration of fast, cost-effective gas sensors are addressed and discussed in this book.